Recht van Eigendom and Inlandsch Eigendom: A Study of Landownership in Colonial Indonesia - Harto Juwono; Nico A. Van Horn (Diponegoro University, 2025)
This article aims to elucidate the existence of two distinct forms of land property rights within the colonial civil law system in Indonesia. By doing so, it seeks to identify the historical origins of issues encountered in contemporary civil law cases. These issues, which are deeply rooted in colonial legal practices, can be better understood by tracing the development of two parallel regimes of property rights: Western civil property rights and indigenous property rights. To examine the origins of these problems, this study employs the historical method, which consists of four stages, namely heuristics, source criticism, interpretation, and historical reconstruction. The sources used are primarily historical documents, with particular emphasis on their authenticity and reliability. The findings indicate that the colonial civil law system was characterized by a dualism of land property rights, each governed by distinct limitations and regulatory frameworks. This dualism emerged as a result of ambiguities and inconsistencies in colonial policies concerning indigenous land ownership.